Machine Learning Techniques and Data Science 2021
DOI: 10.5121/csit.2021.111815
|View full text |Cite
|
Sign up to set email alerts
|

BurnoutWords - Detecting Burnout for a Clinical Setting

Abstract: Burnout, a syndrome conceptualized as resulting from major workplace stress that has not been successfully managed, is a major problem of today's society, in particular in crisis times such as a global pandemic situation. Burnout detection is hard, because the symptoms often overlap with other diseases and syndromes. Typical clinical approaches are using inventories to assess burnout for their patients, even though free-text approaches are considered promising. In research of natural language processing (NLP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A first attempt of working with clinical data to detect burnout has shown promising results. By presenting a dataset from real-world burnout patient data, Nath and Kurpicz-Briki ( 2021 ) managed to go beyond typical burnout detection approaches, which usually includes the use of inventories with scaling questions and worked on applying NLP to mental health. The dataset consisted of data extracted from German-language interviews with burnout patients, a control group, and experts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first attempt of working with clinical data to detect burnout has shown promising results. By presenting a dataset from real-world burnout patient data, Nath and Kurpicz-Briki ( 2021 ) managed to go beyond typical burnout detection approaches, which usually includes the use of inventories with scaling questions and worked on applying NLP to mental health. The dataset consisted of data extracted from German-language interviews with burnout patients, a control group, and experts.…”
Section: Discussionmentioning
confidence: 99%
“…To measure burnout risk, the metric is based on low valence and dominance and high arousal (Mäntylä et al, 2016 ). In other work, a first attempt to detect burnout based on patient and expert interviews in the German language were done; it was found that a combination of NLP and machine learning techniques in this field leads to promising results (Nath and Kurpicz-Briki, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data set: An extended version of the data set from [9] consisting of texts of the following three classes was used: (i) Burnout (ii) Depression (online testimonials, transcripts of documentaries, online forums) and (iii) Control. Each category contains anonymized texts based on publicly available data originating from or having a strong relation to individuals suffering from burnout, depression or none of them (control group).…”
Section: Methodsmentioning
confidence: 99%
“…44 Similarly, attempts have been made to detect burnout by analyzing the subject's speech content extracted from interview records. 45 The same potential for automation exists for stress assessment interviews. By collecting a large amount of highquality data in a standardized manner, it is possible to automate some aspects of the procedure, thereby reducing the burden on occupational health staff.…”
Section: Practical Implicationsmentioning
confidence: 99%